Brief interventions targeting long‐term benzodiazepine and Z‐drug use in primary care: a systematic review and meta‐analysis. (11th February 2020) - Lynch, Tom; Ryan, Cristín; Hughes, Carmel M.; Presseau, Justin; van Allen, Zachary M.; Bradley, Colin P.; Cadogan, Cathal A.
Abstract: Aims: To assess the effectiveness of brief interventions in primary care aimed at reducing or discontinuing long‐term benzodiazepine/Z‐drug (BZRA) use. Method: Systematic review of randomized controlled trials of brief interventions in primary care settings aimed at reducing or discontinuing long‐term BZRA use in adults taking BZRAs for ≥ 3 months. Four electronic databases were searched: PubMed, EMBASE, PsycINFO and CENTRAL. The primary outcome was BZRA use, classified as discontinuation or reduction by ≥ 25%. The Theoretical Domains Framework (TDF) was used to retrospectively code behavioural determinants targeted by the interventions. The Behaviour Change Technique (BCT) Taxonomy was used to identify the interventions' active components. Study‐specific estimates were pooled, where appropriate, to yield summary risk ratios (RRs) and 95% confidence intervals (CIs). Pearson's correlations were used to determine the relationship between intervention effect size and the results of both the TDF and BCT coding. Results: Eight studies were included ( n  = 2071 patients). Compared with usual care, intervention patients were more likely to have discontinued BZRA use at 6 months (eight studies, RR = 2.73, 95% CI = 1.84–4.06) and 12 months post‐intervention (two studies, RR = 3.41, 95% CI = 2.22–5.25). TDF domains 'knowledge', 'memory, attention and decision processes', 'environmental context and resources' and 'social influences' were identified as having been included in every intervention. Commonly identified BCTs included 'information about health consequences', 'credible source' and 'adding objects to the environment'. There was no detectable relationship between effect size and the results of either the TDF or BCT coding. Conclusion: Brief interventions delivered in primary care are more effective than usual care in reducing and discontinuing long‐term benzodiazepine/Z‐drug use.